2022
DOI: 10.1371/journal.pone.0269919
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to insulin therapy and associated factors among type 1 and type 2 diabetic patients on follow up in Madda Walabu University Goba Referral Hospital, South East Ethiopia

Abstract: Background Non-adherence to insulin therapy is a major global public health issue that has a causal relationship with increased diabetic complications that leads to further increase in the health care cost. However, adherence to insulin therapy and associated factors among diabetic mellitus (DM) patients are still not studied adequately in Ethiopia. Objective To assess the adherence to insulin therapy and associated factors among type 1 and type 2 diabetic patients on follow-up at Madda Walabu University—Gob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…For instance, studies have shown usage rates of 85.6% in various countries, underscoring the preference for pens due to their ease of use and less painful injections (23). Despite the availability of advanced devices, the reliance on syringes remains high in this study, which may reflect local availability, cost considerations, or lack of patient and provider awareness about alternative options (18). Interestingly, the study noted that a significant proportion of participants (66.3%) used oral anti-diabetic medication alongside insulin, highlighting the dual approach in managing type 2 diabetes.…”
Section: Discussionmentioning
confidence: 76%
“…For instance, studies have shown usage rates of 85.6% in various countries, underscoring the preference for pens due to their ease of use and less painful injections (23). Despite the availability of advanced devices, the reliance on syringes remains high in this study, which may reflect local availability, cost considerations, or lack of patient and provider awareness about alternative options (18). Interestingly, the study noted that a significant proportion of participants (66.3%) used oral anti-diabetic medication alongside insulin, highlighting the dual approach in managing type 2 diabetes.…”
Section: Discussionmentioning
confidence: 76%
“…A study by Chefik et al, (2022) found that respondents who had a more positive attitude towards insulin therapy had up to 4.55 times greater adherence to insulin therapy than respondents who had a less positive attitude [7]. The study also found that the adherence rate to insulin therapy was 121 (38.9%), mainly due to a diabetes diagnosis period of more than 15 years, poor attitude towards insulin therapy, and suffering from type 2 diabetes, in addition, the absence of a home blood glucose measuring device and poor physical condition, knowledge of insulin therapy, adherence to regular visits to the hospital, and taking two types of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, diabetic patients who are not adherent to insulin therapy may lose control of blood sugar levels more often than patients who are adherent [6]. To provide efficient treatment, minimize complications from other diseases, and improve the quality of life of diabetic patients to maintain a stable condition, it is important to identify patients who do not adhere to the prescribed regimen [7]. Improving adherence to optimize treatment outcomes can help individuals with diabetes mellitus avoid problems [8].…”
Section: Introductionmentioning
confidence: 99%